Solid electrolyte coated ternary positive electrode material as well as preparation method and application thereof

By using LiB3H8 material to coat the ternary positive electrode material in solid-state lithium-ion batteries, the problems of poor material interface compatibility and low lithium ion diffusion coefficient are solved, and the cycle retention rate, specific capacity and rate performance of the battery are significantly improved.

CN119461511AActive Publication Date: 2025-02-18GEM WUXI ENERGY MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411609216.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The existing ternary materials for solid-state lithium-ion batteries have poor compatibility with solid electrolytes and low lithium ion diffusion coefficient, resulting in poor circulation retention, specific capacity and rate performance of the battery.

Method used

The solid electrolyte LiB3H8 material is used as the cladding layer, and a tight cladding structure is formed by mixing it with the ternary material and performing a second sintering treatment under an inert atmosphere to improve the lithium ion diffusion rate.

Benefits of technology

The diffusion rate of lithium ions is improved, the cycle retention rate, specific capacity and rate performance of the battery are improved, and the compatibility of ternary materials and solid electrolytes is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461511A_ABST
    Figure CN119461511A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery positive electrode materials, in particular to a solid electrolyte coated ternary positive electrode material and a preparation method and application thereof. The preparation method of the solid electrolyte coated ternary positive electrode material comprises the following steps: weighing a nickel-cobalt-manganese hydroxide precursor according to the stoichiometric ratio of the ternary material, and uniformly mixing the nickel-cobalt-manganese hydroxide precursor with a lithium source to obtain a mixture; placing the mixture in an oxygen-containing atmosphere, and carrying out first sintering treatment to obtain a ternary material; a LiB3H8 material is obtained; and uniformly mixing the ternary material with a LiB3H8 material, and carrying out secondary sintering treatment in an inert atmosphere to obtain the LiB3H8 / LiB3H8 composite material. According to the invention, the solid electrolyte LiB3H8 material is used as a coating layer, and meanwhile, after the ternary material and the LiB3H8 material are mixed and coated, surface coating fusion is carried out in an inert atmosphere, so that the diffusion rate of lithium ions between the positive electrode material and the electrolyte is improved, and the cycle retention rate, the specific capacity and the rate capability of the battery material are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cathode materials for lithium-ion batteries, and particularly relates to a solid electrolyte-coated ternary cathode material, a preparation method thereof, and an application thereof. Background Art

[0002] Compared with liquid batteries, solid-state batteries have the following advantages: 1) Higher safety: Solid electrolytes are not flammable and have better stability and mechanical properties at high temperatures; 2) Higher energy density: Solid electrolytes have a wider electrochemical window, reducing side reactions with electrode materials and broadening the range of available electrode materials; 3) Longer cycle life: Solid electrolytes are not volatile and there is no leakage problem.

[0003] Currently, the cathode materials of commercialized lithium-ion batteries mainly use phosphate materials and ternary materials. Among them, ternary materials have the advantages of having many lithium ions available for deintercalation, high energy density, and good cycle performance. However, the ternary materials for solid-state batteries still have problems of poor compatibility between the material interface and the solid electrolyte and low lithium ion diffusion coefficient, which affect the diffusion rate of lithium ions between the cathode material and the electrolyte, and further affect the electrochemical properties such as the cycle retention rate, specific capacity, and rate performance of the battery. Summary of the Invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects that the ternary materials for existing solid-state batteries have poor compatibility between the material interface and the solid electrolyte and low lithium ion diffusion coefficient, resulting in poor cycle retention rate, specific capacity, and rate performance of the battery, so as to provide a solid electrolyte-coated ternary cathode material, a preparation method thereof, and an application thereof to solve the above problems.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A preparation method of a solid electrolyte-coated ternary cathode material, comprising: weighing a nickel-cobalt-manganese hydroxide precursor and a lithium source according to the stoichiometric ratio of the ternary material and mixing them evenly to obtain a mixed material; placing the mixed material in an oxygen-containing atmosphere for a first sintering treatment to obtain a ternary material; obtaining a LiB3H8 material; mixing the ternary material and the LiB3H8 material evenly and placing them in an inert atmosphere for a second sintering treatment to obtain the product.

[0007] Preferably, the chemical formula of the ternary material is Li a Ni x Co y Mn 1-x-y O2, where 1.0 ≤ a ≤ 1.1, 0.5 < x < 1, 0 < y < 0.5, x + y < 1; preferably LiNi 0.9 Co 0.05 Mn 0.05 O2.

[0008] Preferably, the molar ratio of the ternary material to the LiB3H8 material is 10:(0.2-2.0);

[0009] And / or, the lithium source comprises lithium hydroxide;

[0010] And / or, the oxygen-containing atmosphere is oxygen or air.

[0011] Preferably, the temperature of the first sintering treatment is 600-800°C, preferably 700°C;

[0012] And / or, the heat preservation time of the first sintering treatment is 8-12 hours, preferably 10 hours.

[0013] Preferably, the temperature of the second sintering treatment is 400-500°C, preferably 450°C;

[0014] And / or, the heat preservation time of the second sintering treatment is 4-6 hours, preferably 5 hours;

[0015] And / or, the inert atmosphere is nitrogen and / or argon.

[0016] Preferably, the process of obtaining the LiB3H8 material comprises: adding nano lithium powder to a tetrahydrofuran solution of borane to react in an anhydrous and oxygen-free environment.

[0017] Preferably, the concentration of the borane tetrahydrofuran solution is 0.5-1.5 mol / L, preferably 1 mol / L;

[0018] And / or, based on the molar amount of the nano lithium powder being 5 mol, the volume of the tetrahydrofuran solution of borane is 15-20 L, preferably 15 L.

[0019] Preferably, the reaction temperature is room temperature;

[0020] And / or, the reaction time is 6-10 hours, preferably 8 hours;

[0021] And / or, stirring is performed while reacting.

[0022] The present invention also provides a solid electrolyte coated ternary positive electrode material, which is prepared by the above-mentioned preparation method of the solid electrolyte coated ternary material.

[0023] The present invention also provides a solid-state lithium-ion battery, which comprises the above-mentioned solid-state electrolyte-coated ternary positive electrode material.

[0024] In the present invention, the room temperature is 20-30°C, preferably 25°C;

[0025] In the present invention, after the nano lithium powder is added to the tetrahydrofuran solution of borane for reaction, it is filtered to remove the insoluble matter and the filtrate is concentrated to remove the solvent, washed, and vacuum concentrated to remove the solvent. The washing agent used in the washing is toluene.

[0026] The technical solution of the present invention has the following advantages:

[0027] 1. A method for preparing a solid electrolyte coated ternary positive electrode material, comprising: weighing a nickel-cobalt-manganese hydroxide precursor and a lithium source according to the stoichiometric ratio of the ternary material to obtain a mixture; placing the mixture in an oxygen-containing atmosphere for a first sintering treatment to obtain a ternary material; obtaining a LiB3H8 material; mixing the ternary material with the LiB3H8 material and placing them in an inert atmosphere for a second sintering treatment. The present invention uses a solid electrolyte LiB3H8 material as a coating layer, which acts as a lithium ion diffusion bridge between the positive electrode material and the solid electrolyte, which not only improves the compatibility of the ternary material interface with the solid electrolyte, but also uses the LiB3H8 material to provide a surface multidimensional ion diffusion path, thereby increasing the diffusion rate of lithium ions between the positive electrode material and the electrolyte (the diffusion rate can be indirectly reflected by the rate performance), thereby improving the cycle retention rate, specific capacity and rate performance of the battery material.

[0028] At the same time, the synthesis process of the ternary material needs to be carried out in an oxidizing atmosphere, while the synthesis process of the LiB3H8 material needs to avoid contact with oxygen. Since the synthesis atmospheres of the two are different, it is impossible to realize the in-situ coating of the LiB3H8 material in the process of synthesizing the ternary material, and it is necessary to synthesize in steps and then carry out mixed coating. However, simple mixed coating will have the problem that the solid electrolyte is not tightly bonded to the surface of the ternary positive electrode material and there are gaps, so that lithium ions cannot be stably transferred, resulting in a low lithium ion diffusion rate. Based on this, the present invention performs surface coating fusion under an inert atmosphere after the ternary material and the LiB3H8 material are mixed and coated, so as to enhance the ability of lithium ions to enter the solid electrolyte after being deintercalated from the surface of the ternary material. Different from ordinary surface contact coating, due to the different synthesis atmosphere, the LiB3H8 material undergoes solid-solid fusion contact with the surface of the ternary material after synthesis. The contact surface is tight and firm, and the lithium ion migration transition is smoother. At the same time, during the cycle process, the lattice volume change and lattice distortion after the material releases lithium ions lead to increased volume change particle stress, and the fusion generates a firm interface, which is not prone to interface separation, thus avoiding the common problem of lithium ions being unable to diffuse after interface separation in solid-state lithium-ion batteries, and further improving the cycle retention rate, capacity and rate performance of battery materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 This is a SEM morphology image of a solid electrolyte coated ternary cathode material obtained in Example 1 of the present invention;

[0031] Figure 2 This is a SEM morphology image of the positive electrode material prepared in Comparative Example 1 of the present invention;

[0032] Figure 3 It is a cycle test chart of Examples 1-3 of the present invention and Comparative Examples 1-4. DETAILED DESCRIPTION

[0033] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0034] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0035] Example 1

[0036] This embodiment provides a method for preparing a solid electrolyte coated ternary positive electrode material, and the specific steps are as follows:

[0037] 1) Weigh 10 mol LiOH, 10.0 mol Ni 0.9 Co 0.05 Mn 0.05 (OH)2 and mixed evenly, placed in an oxygen atmosphere, heated to 700℃ for 10h, cooled in the furnace and crushed through a 250-mesh sieve to obtain the ternary positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 O2.

[0038] 2) In a glove box (anhydrous and oxygen-free environment), 5 mol of nano lithium powder was placed in a schlenk reaction bottle, 15 L of 1 mol / L borane tetrahydrofuran solution (THF·BH3) was added, and the reaction was stirred continuously at room temperature (25°C) for 8 hours, and the insoluble matter was filtered out, and the filtrate was concentrated to remove the solvent to obtain a solid and washed with toluene, and finally vacuum concentrated to remove the solvent to obtain LiB3H8, and the material obtained in step 2) was subjected to elemental analysis, and the test results are shown in Table 1 below:

[0039] Table 1

[0040]

[0041]

[0042] It can be seen from Table 1 that the molar ratio of the synthesized solid electrolyte Li:B:H=1:2.90:7.86. Taking into account the instrument test error, the synthesized solid electrolyte material is close to LiB3H8.

[0043] 3) Weigh 1 mol of LiB3H8 obtained in step 2) and 10 mol of the ternary positive electrode material LiNi obtained in step 1) 0.9 Co 0.05 Mn 0.05 After mixing evenly, place it in a nitrogen atmosphere, heat it to 450℃ and keep it for 5h, cool it in the furnace and crush it through a 250-mesh sieve to obtain a solid electrolyte-coated ternary positive electrode material, and its SEM morphology is as follows: Figure 1 shown.

[0044] Example 2

[0045] This embodiment provides a method for preparing a solid electrolyte coated ternary positive electrode material, and the specific steps are as follows:

[0046] 1) Weigh 10 mol LiOH, 10.0 mol Ni 0.9 Co 0.05 Mn 0.05 (OH)2 and mixed evenly, placed in an oxygen atmosphere, heated to 700℃ for 10h, cooled in the furnace and crushed through a 250-mesh sieve to obtain the ternary positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 O2;

[0047] 2) In a glove box (anhydrous and oxygen-free environment), 5 mol of nano lithium powder was placed in a schlenk reaction bottle, 15 L of 1 mol / L borane tetrahydrofuran solution (THF·BH3) was added, and the reaction was stirred continuously at room temperature (25°C) for 8 hours, and the insoluble matter was filtered out, and the filtrate was concentrated to remove the solvent to obtain a solid, which was washed with toluene, and finally vacuum concentrated to remove the solvent to obtain LiB3H8, and the material obtained in step 2) was subjected to elemental analysis, and the test results are shown in Table 1;

[0048] 3) Weigh 2 mol of LiB3H8 obtained in step 2) and 10 mol of the ternary positive electrode material LiNi obtained in step 1) 0.9 Co 0.05 Mn 0.05 O2 and mixed evenly, placed in a nitrogen atmosphere, heated to 450 ° C and kept warm for 5 hours, cooled with the furnace and crushed through a 250-mesh sieve to obtain a solid electrolyte-coated ternary positive electrode material.

[0049] Example 3

[0050] This embodiment provides a method for preparing a solid electrolyte coated ternary positive electrode material, and the specific steps are as follows:

[0051] 1) Weigh 10 mol LiOH, 10.0 mol Ni 0.9 Co 0.05 Mn 0.05 (OH)2 and mixed evenly, placed in an oxygen atmosphere, heated to 700℃ for 10h, cooled in the furnace and crushed through a 250-mesh sieve to obtain the ternary positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 O2;

[0052] 2) In a glove box (anhydrous and oxygen-free environment), 5 mol of nano lithium powder was placed in a schlenk reaction bottle, 15 L of 1 mol / L borane tetrahydrofuran solution (THF·BH3) was added, and the reaction was stirred continuously at room temperature (25°C) for 8 hours, and the insoluble matter was filtered out, and the filtrate was concentrated to remove the solvent to obtain a solid, which was washed with toluene, and finally vacuum concentrated to remove the solvent to obtain LiB3H8, and the material obtained in step 2) was subjected to elemental analysis, and the test results are shown in Table 1;

[0053] 3) Weigh 0.2 mol of LiB3H8 obtained in step 2) and 10 mol of the ternary positive electrode material LiNi obtained in step 1) 0.9 Co 0.05 Mn 0.05O2 and mixed evenly, placed in a nitrogen atmosphere, heated to 450 ° C and kept warm for 5 hours, cooled with the furnace and crushed through a 250-mesh sieve to obtain a solid electrolyte-coated ternary positive electrode material.

[0054] Comparative Example 1

[0055] This comparative example provides a method for preparing a ternary positive electrode material, and the specific steps are as follows:

[0056] Weigh 10 mol LiOH, 10.0 mol Ni 0.9 Co 0.05 Mn 0.05 (OH)2 and mixed evenly, placed in an oxygen atmosphere, heated to 700℃ for 10h, cooled in the furnace and crushed through a 250-mesh sieve to obtain the ternary positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 O2, its SEM morphology is as follows Figure 2 shown.

[0057] Comparative Example 2

[0058] This comparative example provides a method for preparing an oxide-coated ternary positive electrode material, and the specific steps are as follows:

[0059] 1) Weigh 10 mol LiOH, 10.0 mol Ni 0.9 Co 0.05 Mn 0.05 (OH)2 and mixed evenly, placed in an oxygen atmosphere, heated to 700℃ for 10h, cooled in the furnace and crushed through a 250-mesh sieve to obtain the ternary positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 O2;

[0060] 2) In a glove box (anhydrous and oxygen-free environment), 5 mol of nano-lithium powder was placed in a Schlenk reaction bottle, and 15 L of a 1 mol / L borane tetrahydrofuran solution (THF·BH3) was added. The reaction was stirred at room temperature (25°C) for 8 hours, and the insoluble matter was filtered out. The filtrate was concentrated to remove the solvent to obtain a solid, which was washed with toluene, and finally vacuum concentrated to remove the solvent to obtain LiB3H8;

[0061] 3) Weigh 1 mol of LiB3H8 obtained in step 2) and the ternary positive electrode material LiNi obtained in step 1) 0.9 Co 0.05 Mn 0.05 O2 and mix evenly, place it in an oxygen atmosphere, heat it to 450℃ and keep it for 5h, cool it with the furnace and grind it through a 250-mesh sieve to obtain an oxide-coated ternary positive electrode material.

[0062] Comparative Example 3

[0063] This comparative example provides a method for preparing a ternary positive electrode material, and the specific steps are as follows:

[0064] 1) Weigh 10 mol LiOH, 10.0 mol Ni 0.9 Co 0.05 Mn 0.05 (OH)2 and mixed evenly, placed in an oxygen atmosphere, heated to 700℃ for 10h, cooled in the furnace and crushed through a 250-mesh sieve to obtain the ternary positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 O2;

[0065] 2) Weigh 1 mol of LiBH4 and the ternary cathode material LiNi obtained in step 1) 0.9 Co 0.05 Mn 0.05 O2 and mixed evenly, placed in a nitrogen atmosphere, heated to 450 ° C and kept warm for 5 hours, cooled with the furnace and crushed through a 250-mesh sieve to obtain LiBH4-coated ternary positive electrode material.

[0066] Comparative Example 4

[0067] This comparative example provides a method for preparing a ternary positive electrode material, and the specific steps are as follows:

[0068] 1) Weigh 10 mol LiOH, 10.0 mol Ni 0.9 Co 0.05 Mn 0.05 (OH)2 and mixed evenly, placed in an oxygen atmosphere, heated to 700℃ for 10h, cooled in the furnace and crushed through a 250-mesh sieve to obtain the ternary positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 O2;

[0069] 2) In a glove box (anhydrous and oxygen-free environment), 5 mol of nano-lithium powder was placed in a Schlenk reaction bottle, and 15 L of a 1 mol / L borane tetrahydrofuran solution (THF·BH3) was added. The reaction was stirred at room temperature (25°C) for 8 hours, and the insoluble matter was filtered out. The filtrate was concentrated to remove the solvent to obtain a solid, which was washed with toluene, and finally vacuum concentrated to remove the solvent to obtain LiB3H8;

[0070] 3) Weigh 1 mol of LiB3H8 obtained in step 2) and the ternary positive electrode material LiNi obtained in step 1) 0.9 Co 0.05 Mn0.05 O2 and mixed evenly, placed in a 100 ° C vacuum box to dry for 1 day, crushed through a 250 mesh sieve to obtain a simply mixed and coated solid electrolyte coated ternary positive electrode material.

[0071] Test Example 1

[0072] The electrochemical performance test was conducted on the positive electrode materials prepared in the above embodiments and comparative examples. The electrochemical performance test steps are as follows: weigh the positive electrode material, carbon black and polyvinylidene fluoride (PVDF) in a mass ratio of 95:2.5:2.5, add solvent N-methylpyrrolidone (NMP) in a solid-liquid ratio of 2:1 to prepare positive electrode slurry, evenly coat the slurry on aluminum foil, bake at 105°C for 2h, cut the baked electrode pieces and put them into a tablet press for compaction (compacted density is 3.2g / cm 3 ), cut out small discs, assemble them in a nitrogen atmosphere, where the water and oxygen content is less than 0.1ppm, put the small discs into the positive side of the buckle battery shell, with the coated side facing the positive electrode, and add polyacrylonitrile (PAN) + Li7La3Zr2O 12 (LLZO) (the mass ratio of PAN:LLZO is 1:9), and then put in the negative electrode sheet (pure lithium sheet), gasket, spring, buckle the negative electrode shell, and package it into a CR2032 button battery. Among them, the charge and discharge system: the charging cut-off voltage is 4.3V, the discharge cut-off voltage is 3.0V; the first cycle is 0.1C charging, 0.1C discharging; the second cycle is 0.5C charging, 0.5C discharging; the third cycle is 1.0C charging, 1.0C discharging; then 1C charging and 1C discharging cycles 500 times to test the cycle retention rate (such as Figure 3 The test results are shown in Table 2.

[0073] Table 2

[0074]

[0075] As can be seen from Table 2, the 0.1C discharge specific capacity of the solid electrolyte coated ternary positive electrode material prepared by the present invention is greater than or equal to 212.0 mAh / g, the 0.5C discharge specific capacity is greater than or equal to 201.3 mAh / g, the 1C discharge specific capacity is greater than or equal to 196.5 mAh / g, and the 500 cycle performance is greater than or equal to 90.78%.

[0076] By comparing Example 1 and Comparative Example 1, it can be seen that the ternary material of this embodiment is coated with a solid electrolyte and applied to a solid-state battery. Since the positive electrode material is coated with a solid electrolyte in advance, it has good contact with the electrolyte in the solid-state battery. After lithium ions escape from the ternary positive electrode body, they pass through the three-dimensional pathway of the solid electrolyte coated on the surface and smoothly enter the electrolyte of the solid-state battery. Therefore, the material has high capacity and good cycle performance.

[0077] By comparing Example 1 and Comparative Example 2, it can be seen that after the LiB3H8 material in Comparative Example 2 is coated, it is sintered in an oxygen atmosphere, the coated solid electrolyte is oxidized, the crystal form of the surface coating changes, and the three-dimensional diffusion path of lithium ions is lost, resulting in a decrease in capacity and cycle.

[0078] By comparing Example 1 and Comparative Example 3, it can be seen that after the LiBH4 material in Comparative Example 3 is coated, the ion conductivity of the coating LiBH4 is weak, which hinders the lithium ions from entering the electrolyte of the battery, resulting in reduced capacity and cycle.

[0079] By comparing Example 1 and Comparative Example 4, it can be seen that after the LiB3H8 material in Comparative Example 4 is coated, the treatment method is a vacuum oven with a sintering temperature of 100°C, which is insufficient to fuse the LiB3H8 and the ternary material matrix. There is a physical gap on the contact surface, and the interface ion conductivity is poor, which seriously hinders the lithium ions from entering the coated electrolyte, resulting in reduced capacity and cycle.

[0080] Depend on Figure 1 and Figure 2 By comparison, it can be seen that in the positive electrode material prepared in Example 1, the solid electrolyte LiB3H8 is tightly coated on the surface of the ternary material.

[0081] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing a solid electrolyte coated ternary positive electrode material, characterized in that: include: According to the stoichiometric ratio of the ternary material, a nickel-cobalt-manganese hydroxide precursor and a lithium source are weighed and mixed to obtain a mixture; the mixture is placed in an oxygen-containing atmosphere for a first sintering treatment to obtain a ternary material; LiB3H8 material is obtained; the ternary material and the LiB3H8 material are mixed and placed in an inert atmosphere for a second sintering treatment to obtain the mixture.

2. The preparation method according to claim 1, characterized in that: The chemical formula of the ternary material is Li a Ni x Co y Mn 1-x-y O2, where 1.0 ≤ a ≤ 1.1, 0.5 < x < 1, 0 < y < 0.5, and x + y < 1; preferably LiNi 0.9 Co 0.05 Mn 0.05 O2.

3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of the ternary material to the LiB3H8 material is 10:(0.2-2.0); And / or, the lithium source comprises lithium hydroxide; And / or, the oxygen-containing atmosphere is oxygen or air.

4. The preparation method according to any one of claims 1 to 3, characterized in that The temperature of the first sintering treatment is 600-800°C, preferably 700°C; And / or, the heat preservation time of the first sintering treatment is 8-12 hours, preferably 10 hours.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The temperature of the second sintering treatment is 400-500°C, preferably 450°C; And / or, the heat preservation time of the second sintering treatment is 4-6 hours, preferably 5 hours; And / or, the inert atmosphere is nitrogen and / or argon.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The process of obtaining the LiB3H8 material includes: adding nano lithium powder to a tetrahydrofuran solution of borane to react in an anhydrous and oxygen-free environment.

7. The preparation method according to claim 6, characterized in that: The concentration of the borane tetrahydrofuran solution is 0.5-1.5 mol / L, preferably 1 mol / L; And / or, based on the molar amount of the nano lithium powder being 5 mol, the volume of the tetrahydrofuran solution of borane is 15-20 L, preferably 15 L.

8. The preparation method according to claim 6 or 7, characterized in that: The reaction temperature is room temperature; And / or, the reaction time is 6-10 hours, preferably 8 hours; And / or, stirring is performed while reacting.

9. A solid electrolyte coated ternary cathode material, characterized in that: The solid electrolyte-coated ternary material is prepared by the preparation method of the solid electrolyte-coated ternary material according to any one of claims 1 to 8.

10. A solid-state lithium-ion battery, characterized in that: The solid-state lithium-ion battery comprises the solid-state electrolyte-coated ternary positive electrode material according to claim 9.

Citation Information

Patent Citations

  • Synthesis method of LiB3H8 (boron hydride of lithium)

    CN107473184A

  • Preparation method and application of surface-fully-coated high-nickel single-crystal ternary material

    CN114267841A

  • Ternary positive electrode material coated with lithium-containing oxide and preparation method of ternary positive electrode material

    CN114784238A

  • Surface-coated ternary positive electrode material and preparation method thereof

    CN116544372A

  • Composite ternary positive electrode material, preparation method thereof and lithium ion battery containing composite ternary positive electrode material

    CN118800892A